(untitled) (Journal of the College of Basic Education, 2025)
As the time of arrival of Europeans to North America and its exploration, there were a huge number of Indian tribes inhabiting vast areas of the United States and speaking different languages. The most important of these tribes is the Sioux tribe, which is one of the most famous and largest Indian tribes. It was known for its skill and chivalry and considered horses a source of wealth. It practiced horse trade with the help of the Spanish, which enabled it to improve its living conditions. Despite its mixing with travelers and traders, it was able to preserve its customs and culture from European influence. Therefore, through this research, we will address the roots of the Sioux tribe, and shed light on the economic, social and religious aspects.